Does the EU need a common immigration and asylum policy? - Panu Poutvaara (EconPol Forum, 2025)
The main challenge in high-skilled immigration is to make Europe sufficiently attractive. Employers should be trusted to evaluate who is qualified to work in non-regulated professions. Migration Partnerships ease low-skilled labor migration and help combat irregular migration. Distributing asylum seekers to less welcoming countries could backfire and trap them in poverty. Instead, the EU should develop a matching mechanism for asylum seekers and host countries.
Keywords: 330